Group I metabotropic glutamate receptors generate two types of intrinsic membrane oscillations in hippocampal oriens/alveus interneurons. (1st September 2018) - Govindaiah, Gubbi; Kang, Young-Jin; Lewis, Hannah Elisabeth Smashey; Chung, Leeyup; Clement, Ethan M.; Greenfield, Lazar John; Garcia-Rill, Edgar; Lee, Sang-Hun
Abstract: GABAergic interneurons in the hippocampus are critically involved in almost all hippocampal circuit functions including coordinated network activity. Somatostatin-expressing oriens-lacunosum moleculare (O-LM) interneurons are a major subtype of dendritically projecting interneurons in hippocampal subregions (e.g., CA1), and express group I metabotropic glutamate receptors (mGluRs), specifically mGluR1 and mGluR5 . Group I mGluRs are thought to regulate hippocampal circuit functions partially through GABAergic interneurons. Previous studies suggest that a group I/II mGluR agonist produces slow supra-threshold membrane oscillations (<0.1 Hz), which are associated with high-frequency action potential (AP) discharges in O-LM interneurons. However, the properties and underlying mechanisms of these slow oscillations remain largely unknown. We performed whole-cell patch-clamp recordings from mouse interneurons in the stratum oriens/alveus (O/A interneurons) including CA1 O-LM interneurons. Our study revealed that the selective mGluR1/5 agonist (S)-3, 5-dihydroxyphenylglycine (DHPG) induced slow membrane oscillations (<0.1 Hz), which were associated with gamma frequency APs followed by AP-free perithreshold gamma oscillations. The selective mGluR1 antagonist (S)-(+)-α-Amino-4-carboxy-2-methylbenzeneacetic acid (LY367385) reduced the slow oscillations, and the selective mGluR5 antagonist 2-methyl-6-(phenylethynyl)pyridine hydrochloride (MPEP) partially blocked them. Blockade of nonselective cation-conducting transient receptor potential channels, L-type Ca 2+ channels, or ryanodine receptors all abolished the slow oscillations, suggesting the involvement of multiple mechanisms. Our findings suggest that group I mGluR activation in O/A interneurons may play an important role in coordinated network activity, and O/A interneuron vulnerability to excitotoxicity, in disease states like seizures, is at least in part due to an excessive rise in intracellular Ca 2+ . Highlights: Group I mGluR activation in O/A interneurons produced slow membrane oscillations. Slow oscillations were associated with gamma oscillations. Slow oscillations were mediated by both mGluR1 and mGluR5 . TRP channels and L-type Ca 2+ channels were involved in the slow oscillations. Ryanodine receptors were also involved in the slow oscillations.